Potential of Chlorella sp. grown in parboiled effluent in combination with organic or inorganic fertilizers on growth and yield of brinjal (Solanum melongina) - Ruwangi, K.H.G.L.; Jeyakumar, K.; Gnanavelrajah, N.; Ketheesan, B. (Faculty of Agriculture, University of Ruhuna, Sri Lanka., 2022)
A study was conducted to assess the potential of Chlorella sp. grown in parboiled effluent as an organic fertilizer. Chlorella sp. was cultivated using parboiled effluent in a raceway reactor for 14 days continuously with constant light intensity (200µmol photons m-2s-1) and constant mixing to optimize the algal growth. The nutrient content (N, P, and K) of Chlorella sp. was determined. A pot experiment was conducted to find the response of Brinjal (Solanum melongina) for different inorganic or organic fertilizer combinations with Chlorella. The design was CRD with eight treatments and three replicates. The treatments were T1 - control, T2 - 100 % inorganic fertilizer (IF), T3 - 100 % cattle manure (CM), T4 - 30 g Chlorella + 100 % inorganic fertilizer except N (IFEN), T5 - 15 g Chlorella + 50 % IFEN, T6 - 15 g Chlorella + 50 % CM, T7 - 20 % Chlorella Foliar spray (FS)+ 50 % IFEN, T8 - 20 % Chlorella FS + 15 g Chlorella + 50% IFEN. The height, leave numbers, the number of flowers per plant, and the yield of Brinjal were recorded. The Chlorella had 25 % of nitrogen, 7.5 % phosphorus, and 0.74 % potassium. All the treatments in the pot experiment gave a similar or higher yield than T2 (100 % IF) except the control. T6 (Chlorella 15 g + 50 % CM) gave the highest yield anyhow no significant difference was observed between T6 and T4 (30g Chlorella + 100 % IFEN). Considering the yield, T6 (Chlorella 15 g + 50 % CM) is the better option in organic combinations while T4 (30g Chlorella + 100 % IFEN) is the better option in inorganic combinations. This study, therefore, highlights the potential of using Chlorella sp. grown in parboiled effluent as a nitrogen source for crop production. Further studies are required to optimize the nutrient supply including phosphorus.
Keywords: Algae; Brinjal; Foliar spray; Organic nutrient source